Optimization of the strength of the efavirenz/lamivudine/abacavir fixed-dose combination for paediatric patients - Bouazza N. (2017)
© The Author 2016. Background: Child-friendly, low-cost, solid, oral fixed-dose combinations (FDCs) of efavirenz with lamivudine and abacavir are urgently needed to improve clinical management and drug adherence for children. Methods: Data were pooled from several clinical trials and therapeutic drug monitoring datasets from different countries. The number of children/observations was 505/3667 for efavirenz. Population pharmacokinetic analyses were performed using a non-linear mixed-effects approach. For abacavir and lamivudine, data from 187 and 920 subjects were available (population pharmacokinetic models previously published). Efavirenz/lamivudine/abacavir FDC strength options assessed were (I) 150/75/150, (II) 120/60/120 and (III) 200/100/200 mg. Monte Carlo simulations of the different FDC strengths were performed to determine the optimal dose within each of the WHO weight bands based on drug efficacy/safety targets. Results: The probability of being within the target efavirenz concentration range 12 h post-dose (1-4 mg/L) varied between 56% and 60%, regardless of FDC option. Option I provided a best possible balance between efavirenz treatment failure and toxicity risks. For abacavir and lamivudine, simulations showed that for option I > 75% of subjects were above the efficacy target. Conclusions: According to simulations, a paediatric efavirenz/lamivudine/abacavir fixed-dose formulation of 150 mg efavirenz, 75 mg lamivudine and 150 mg abacavir provided the most effective and safe concentrations across WHO weight bands, with the flexibility of dosage required across the paediatric population.